Emotional availability in mothers with borderline personality disorder and mothers with remitted major depression is differently associated with psychopathology among school-aged children - Kluczniok, Dorothea; Herpertz, Sabine; Brunner, Romuald (Journal of affective disorders, 2018)
Both, maternal borderline personality disorder (BPD) and maternal major depressive disorder (MDD) are often associated with adverse consequences for children, including increased risk for child behavior problems. Reduced maternal emotional availability might play a critical role in transmitting maternal psychopathology on the child. Our aim was to investigate the association between emotional availability and maternal BPD and MDD in remission (rMDD), and if this interrelatedness mediates the association between maternal mental disorders and child behavior problems.